Blocking cellular N-glycosylation suppresses human cytomegalovirus entry in human fibroblasts. (January 2020) - Zheng, Luping; Li, Huifen; Fu, Li; Liu, Sally; Yan, Qiu; Leng, Sean X.
Abstract: N-glycosylation plays an important role in the pathogenesis of viral infections. However, the role of host cell N-glycosylation in human cytomegalovirus (hCMV) infection remains to be elucidated. In this study, we found that blocking or removal of cellular N-glycosylation by tunicamycin, peptide-N-glycosidase F (PNGase F) treatment, or N-acetylglucosaminyltransferase I (MGAT1) knockdown resulted in suppression of hCMV infection in human fibroblasts. This suppression was reversed following N-glycosylation restoration. Immunofluorescence and flow cytometry analysis showed that blockade of cellular N-glycosylation interfered with hCMV entry rather than binding. Removal of N-glycosylation on epidermal growth factor (EGFR) and integrin β3, two proposed hCMV receptors, blocked their interaction with hCMV glycoproteins B and H. It also suppressed activation of these receptors and downstream integrin β3/Src signaling. Taken together, these results suggest that N-glycosylation of host cell glycoproteins including two proposed hCMV receptors is critical for hCMV entry rather than attachment. They provide novel insights into the biological process important for the early stage of hCMV infection with potential therapeutic implications. Highlights: Cellular N-glycans blocking led to suppression of hCMV infection in human fibroblasts. Blockade of cellular N-glycosylation interfered with hCMV entry rather than binding. N-glycans of hCMV receptor EGFR and integrin β3 are essential to the interaction with hCMV glycoproteins B and H.